Explaining the Widening Education Gap in Mortality among U.S. White Women - Montez, Jennifer Karas (2013)
Over the last half century the gap in mortality across education levels grew in the United States, and since the mid-1980s the growth was especially pronounced among white women. The reasons for the growth among white women are unclear. We investigated three explanations—social-psychological factors, economic circumstances, and health behaviors—for the widening education gap in mortality across 1997-2006 among white women 45-84 years of age. We used data from the National Health Interview Survey Linked Mortality File (N=46,744; deaths=4,053). We found little support for social-psychological factors; however, economic circumstances and health behaviors jointly explained the growing education gap in mortality to statistical nonsignificance. Employment and smoking were the most important individual components. Increasing high school graduation rates, reducing smoking prevalence, and designing work-family policies that help women find and maintain desirable employment may reduce mortality inequalities among women.